Mathematical analysis of an age structured problem modelling phenotypic plasticity in mosquito behaviour - Li, Lin Lin (2019)
This paper presents an age structured problem modelling mosquito blood-feeding plasticity in a natural environment. We first investigate the analytical asymptotic solution through studying the spectrum of an operator A which is the infinitesimal generator of a C 0 -semigroup. Indeed, the study of the spectrum of A per se is interesting. Additionally, we get the existence and nonexistence of nonnegative steady solutions under some conditions.